Maternal obesity and baseline vitamin D insufficiency alter the response to vitamin D supplementation: a double-blind, randomized trial in pregnant women. Issue 3 (8th May 2021) - Alhomaid, Raghad M; Mulhern, Maria S; Strain, Jj; Laird, Eamon; Healy, Martin; Parker, Michael J; McCann, Mary T
ABSTRACT: Background: The achievement of target 25-hydroxyvitamin D [25(OH)D] concentrations in pregnancy may be altered by maternal obesity. Objective: The authors examined the effects of maternal supplementation of 10 μg compared with 20 μg vitamin D3 /d on maternal and umbilical cord 25(OH)D. The secondary aim was to investigate the influence of maternal BMI (in kg/m 2 ) on the response of the primary outcomes. Methods: The authors performed a 2-arm parallel double-blind randomized trial with 240 pregnant women recruited throughout the year in Northern Ireland. Women were stratified by BMI to receive 10 or 20 µg vitamin D3 /d from 12 gestational wk (GW) until delivery. Maternal blood samples collected at 12, 28, and 36 GW and from the umbilical cord were analyzed for total serum 25(OH)D. A total of 166 women completed the study. Results: Mean ± SD 25(OH)D at 36 GW was 80.8 ± 28.2 compared with 94.4 ± 33.2 nmol/L ( P < 0.001) (10 compared with 20 µg vitamin D3 /d, respectively). In those classified with 25(OH)D <50 nmol/L at baseline and assigned 10 µg vitamin D3 /d, mean 25(OH)D concentrations remained <50 nmol/L at 36 GW, whereas those <50 nmol/L at baseline and assigned 20 µg vitamin D3 /d, had mean 25(OH)D concentrations ≥50 nmol/L at 28 and 36 GW. In women with obesity and 25(OH)D <50 nmol/L at baseline,  the related mean umbilical cord 25(OH)D was deficient (<25 nmol/L) in both treatment groups, whereas those with obesity and 25(OH)D ≥50 nmol/L at baseline had an average umbilical cord 25(OH)D between 25 and 50 nmol/L in both treatment groups. Conclusions: Supplementation of 20 µg vitamin D3 /d is needed to attain maternal and umbilical cord 25(OH)D concentrations ≥50 nmol/L on average, in those who start pregnancy with low 25(OH)D concentrations (<50 nmol/L). Under current recommendations, women with obesity and low 25(OH)D in early pregnancy are particularly vulnerable to maintaining a low 25(OH)D concentration throughout pregnancy and having an infant born with deficient 25(OH)D concentrations. This trial was registered at ClinicalTrials.gov as NCT02713009.